Health behaviour and eating habits among foreign students at the Instituto Politécnico de Bragança - Kiss, Benjamin (2014)
Several studies have addressed to assess the eating habits of university students, but only few studies are about the eating habits of foreign students. Previous studies found that the eating habits are changing in a negative way because of the limited availability and poor quality of familiar foods. The objective of this study was to determine the eating habits of the students before their arrival to Portugal. This is the first part of a longitudinal study, our final aim is to establish the changes on the eating habits and health behavior of students from abroad during their scholarship.